In vitro model for study the interaction between tumor and stromal cells - Shkarina, K.A.; Cherednyk, O.V.; Tykhonkova, I.O.; Khoruzhenko, A.I. (Вiopolymers and Cell, 2013)
Aim. To develop a model to study the interaction between tumor and stromal cells in three-dimensional culture. Methods. Cultivation of HeLa cell lines and human dermal fibroblasts in monolayer and three-dimensional culture, immunofluorescent and immunohistochemical analysis. Results. In this work we present an approach based on a direct interaction between the cells of multicellular tumor spheroids and spheroids of fibroblasts. Subsequent immunofluorescence analysis allows to determine an origin of cells in the area of their contact. Conclusions. This model will be useful to study the basic mechanisms of carcinogenesis, and to find targets for anticancer therapy.